MODEL PENGELOLAAN FISKAL RASUL SAW DALAM KONTEKS PENGELOLAAN FISKAL KOTA PALEMBANG - Amri, Hoirul; Jauhari, Muhammad (Universitas Muhammadiyah Palembang, 2018)
This study aims to find out the model of the fiscal application of Rasul SAW in the context of the fiscal management of Palembang City Province. This research was conducted in two stages. Phase I, namely describing Rasul SAW's fiscal management model and implemented it in the management of the fiscal city of Palembang and its implications for the level of security and welfare of the people of Palembang city. Phase II, namely the development of Rasul SAW's fiscal management model, became the model rule for the fiscal management of Palembang city. Fiscal management includes the use of government spending, taxation, and loans to achieve the desired goals in building a country, fiscal management becomes the main tool for the state for welfare, this management is applied by the Prophet Muhammad in Medina. The Prophet Muhammad's fiscal resources consisted of Zakat, Ghanimah, Kharaj, Jizyah, and other sources burupa Usyir. The position of fiscal management plays an important role in the Islamic economic system compared to monetary management, with the prohibition on usury and obligations regarding the importance of fiscal position compared to monetary. The economic and fiscal system applied to the government of Palembang City refers to the policies contained in the Pancasila, the Act, and government regulations both the central government and regional government regulations. The fiscal becomes regional original income (PAD) sourced from; (1) Results of regional tax collection; (2) Regional retreat; (3) Management of regional wealth 4) and others.